TWO STAGE GROWTH OF MICRODIAMOND IN UHP DOLOMITE MARBLE FROM KOKCHETAV MASSIF, KAZAKHSTAN - Ishida H.; Ogasawara Y.; Ohsumi K.; Saito A. (My University, 2003)
The abundance and morphology of microdiamond in dolomite marble from Kumdy-kol in the Kokchetav Massif, are unusual; a previous study estimated the maximum content of diamonds in dolomite marble to be about 2700 carat ton−1. Microdiamond is included primarily in garnet, and occasionally in diopside and phlogopite pseudomorphs after garnet. They are classified into three types on the basis of their morphology: (1) S-type: star-shaped diamond consisting of translucent cores and transparent subhedral to euhedral very fine-grained outer parts; (2) R-type: translucent crystals with rugged surfaces; and (3) T-type: transparent, very fine-grained crystals. The S-type is the most abundant. Micro-Laue diffraction using a 1.6-µm X-ray beam-size demonstrated that the cores of the star-shaped microdiamond represent single crystals. In contrast, the most fine-grained outer parts usually have different orientations compared to the core. Laser–Raman studies indicate that the FWHM (Full Width at Half Maximum) of the Raman band of the core of the S-type diamond is slightly larger than that for the outer parts. Differences in morphology, crystal orientations, and in the FWHM of the Raman band between the core and the fine-grained outer-parts of S-type microdiamond suggest that the star-shaped microdiamond was formed discontinuously in two distinct stages.
Keywords: dolomite marble; Kokchetav Massif; microdiamond; micro-Laue diffraction; ultrahigh-pressure metamorphism